European Dream. ‘Keep bangin’ on the wall’ - CRUZ, Carla (2021)
This paper discusses ideas around European identity, the ideal of free movement, and the building of ‘Fortress Europe’ through artistic work I developed between 2005 and 2006; and endorses feminist theorist Rosi Braidotti’s idea of “becoming minoritarian” as an antidote to constructing an European identity based on old and new xenophobic and racist ideas, supported through my experience of leading the feminist exhibition project All My Independent Wo/men between 2005 and 2013, as a similar project of operating from the margins as a place of potentiality.